2023
DOI: 10.1021/acscatal.2c05504
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylation-Induced Defects in MOF-Derived Ni@C Catalysts for Efficient Chemoselective Hydrogenation of Nitrocyclohexane to Cyclohexanone Oxime

Abstract: In this work, MOF-derived Ni@C catalysts with rich defects were synthesized using a facile thermally decarboxylation-induced defect strategy for nitrocyclohexane (NCH) hydrogenation. It was found that the strong metal–support interaction (SMSI) between the defect-rich carbon and Ni promotes the dispersion of Ni nanoparticles, reduces the Ni particle size, and affects the surface charge state of Ni to form electron-deficient Ni, thus exhibiting outstanding catalytic activity. Additionally, in situ diffuse refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In situ DRIFTS can be used to study the adsorption, activation, and desorption processes of substrate molecules. , The detailed procedures are described in the Supporting Information (Text S3). The in situ DRIFTS result of MOF-808-S in Figure shows that the orbital peak at 1718 cm –1 is ascribed to ν(CO) of acrolein, and the orbital peak at 1475 cm –1 belongs to ν(CC). , Note that MOF-808-S exhibits a significant red shift at the ν (CO) orbitals in comparison with the gaseous acrolein.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In situ DRIFTS can be used to study the adsorption, activation, and desorption processes of substrate molecules. , The detailed procedures are described in the Supporting Information (Text S3). The in situ DRIFTS result of MOF-808-S in Figure shows that the orbital peak at 1718 cm –1 is ascribed to ν(CO) of acrolein, and the orbital peak at 1475 cm –1 belongs to ν(CC). , Note that MOF-808-S exhibits a significant red shift at the ν (CO) orbitals in comparison with the gaseous acrolein.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Yao prepared activated carbon-supported non-noble bimetallic Ni–Cu for NCH hydrogenation to CHO with 87.5% yield and found that Cu could effectively promote Ni nanoparticle dispersion and facilitate Ni 0 formation . Recently, our group synthesized MOF-derived Ni@C catalysts with rich defects and the strong metal–support interaction (SMSI) between the defect-rich carbon and Ni promotes Ni nanoparticles dispersion, reduces the Ni particle size, and affects the surface charge state of Ni to form electron-deficient Ni, hence exhibited outstanding catalytic performance in NCH hydrogenation to CHO . However, MOFs have the disadvantages of complex preparation and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recently, our group synthesized MOF-derived Ni@C catalysts with rich defects and the strong metal−support interaction (SMSI) between the defect-rich carbon and Ni promotes Ni nanoparticles dispersion, reduces the Ni particle size, and affects the surface charge state of Ni to form electron-deficient Ni, hence exhibited outstanding catalytic performance in NCH hydrogenation to CHO. 12 However, MOFs have the disadvantages of complex preparation and high cost.…”
Section: Introductionmentioning
confidence: 99%